Application of Pregnancy Exercise to Pregnant Women's Readiness in Overcoming Back Pain in Pregnant Women Trimester III - Khusnul Nikmah; Fitriana Ikhtiarinawati Fajrin; Lilik Darwati (Healthy-Mu Journal, 2023)
Back pain is a disorder that many pregnant women experience throughout pregnancy until the postnatal period. One effort that can be done to reduce back pain during pregnancy is to do pregnancy exercises. The aim of the study was to determine the effect of pregnancy exercise on the back pain of trimester III pregnant women in Doyomulyo Village, Kembangbahu District, Lamongan Regency. The Quasy Experiment research method uses the one group pre-post test design approach. The sampling technique for this study was Total Sampling, using the Wilcoxon Test with the test results obtained that all respondents experienced a decrease in back pain with a value of p = 0.004 < α 0.05. where the pain intensity before exercise was higher, namely 5.80 (± 1.135) and the pain intensity decreased after pregnancy exercise to 3.10 (± 1.287). Therefore it is highly recommended and recommended for pregnant women, both primigravida and multigravida, from Trimester I to III, to take part in the Pregnant Women Exercise program.